The Soil Water Isotope Storage System (SWISS): An integrated soil water vapor sampling and multiport storage system for stable isotope geochemistry. (15th April 2020) - Havranek, Rachel E.; Snell, Kathryn E.; Davidheiser‐Kroll, Brett; Bowen, Gabriel J.; Vaughn, Bruce
Abstract : Rationale: Soil water stable isotopes are a powerful tool for tracking interactions among the hydrosphere, geosphere, atmosphere, and biosphere. The challenges associated with creating high‐temporal‐resolution soil water stable isotope datasets from a diversity of sites have limited the utility of stable isotope geochemistry in addressing a range of complex problems. A device that can enable further development of high‐temporal‐resolution soil water isotope datasets that are created with minimal soil profile disruption from remote sites would greatly expand the utility of soil water stable isotope analyses. Methods: We designed a method for sampling and storing soil water vapor for stable isotope analysis that leverages recent advances in soil water sampling strategies. Here, we test the reliability of the storage system by introducing water vapor of known oxygen and hydrogen isotopic composition into the storage system, storing the water vapor for a predetermined amount of time, and then measuring the stable isotope composition of the vapor after the storage period. Results: We demonstrate that water vapor stored in our flasks reliably maintains its isotope composition within overall system uncertainty (±0.5‰ for δ 18 O values and ±2.4‰ for δ 2 H values) for up to 30 days. Conclusions: This method has the potential to enable the collection of high‐temporal‐resolution soil water isotope datasets from remote sites that are not accessed daily in a time‐ and cost‐effective manner. All the components used in the system can be easily controlled using open‐source microcontrollers, which will be used in the future to automate sampling routines for remote field deployment. The system is designed to be an open‐source tool for use by other researchers.